Moderating Effect of Quality Delivery on Customer Satisfaction and Loyalty Relationship of Multiple-Use Hotels - Olivar, Kiven G.; Leon, Ariel W. De (Archives of Business Research, 2023)
The main objective of this study was to determine the moderating effect of quality delivery on the relationship between customer satisfaction and loyalty of multiple-use hotels in Davao City, Philippines. Adopted survey questionnaires were given to a sample of 300 customers from various multiple use three star hotels in Davao City. This study employed non-experimental design utilizing descriptive correlation technique. The statistical tools used were mean, Pearson r and hierarchical logistic regression modgraph. Results revealed that the level of customer satisfaction and quality delivery are very high whilst the level of loyalty are found to be high. Further finding revealed that customer satisfaction is related to loyalty. Quality delivery also showed a positive significant relationship to positive significant relationship to loyalty. In determining the moderating effect of quality delivery, results revealed that the quality delivery demonstrated a significant moderating effect on the relationship between customer satisfaction and loyalty of multi-use hotels. The multiple-use hotels who have higher quality delivery to their customers have also higher level of customer satisfaction and loyalty.